Developing electrical properties of postnatal mouse lumbar motoneurons - Durand, Jacques; Filipchuk, Anton; Pambo-Pambo, Arnaud; Amendola, Julien; Borisovna Kulagina, Iryna; Guéritaud, Jean-Patrick (Frontiers in Cellular Neuroscience, 2015)
We studied the rapid changes in electrical properties of lumbar motoneurons between postnatal days 3 and 9 just before mice weight-bear and walk. The input conductance and rheobase significantly increased up to P8. A negative correlation exists between the input resistance and rheobase. Both parameters are significantly correlated with the total dendritic surface area of motoneurons, the largest motoneurons having the lowest input resistance and the highest rheobase. We classified the motoneurons into three groups according to their discharge firing patterns during current pulse injection (transient, delayed onset, sustained). The delayed onset firing type has the highest rheobase and the fastest action potential whereas the transient firing group has the lowest rheobase and the less mature action potential. We found 32% and 10 % of motoneurons with a transient firing at P3-P5 and P8, respectively. About 20% of motoneurons with delayed onset firing were detected at P8. At P9, all motoneurons exhibit a sustained firing. We defined five groups of motoneurons according to their discharge firing patterns in response to ascending and descending current ramps. In addition to the four classical types, we defined a fifth type called transient for the quasi-absence of discharge during the descending phase of the ramp. This transient type represents about 40% between P3-P5 and tends to disappear with age. Types 1 and 2 (linear and clockwise hysteresis) are the most preponderant at P6-P7. Types 3 and 4 (prolonged sustained and counter clockwise hysteresis) emerge at P8-P9. The emergence of type 3 and 4 probably depends on the maturation of L type calcium channels in the dendrites of motoneurons. No correlation was found between groups defined by step or triangular ramp of currents with the exception of transient firing patterns. Our data support the idea that a switch in the electrical properties of lumbar motoneurons might exist in the second postnatal week of life in mice.